2023
DOI: 10.3389/fonc.2022.977111
|View full text |Cite
|
Sign up to set email alerts
|

Tumor burden score dictates prognosis of patients with combined hepatocellular cholangiocarcinoma undergoing hepatectomy

Abstract: BackgroundThe prognostic value of the tumor burden score (TBS) in patients with combined hepatocellular-cholangiocarcinoma (cHCC-CCA) remains unknown. This study aimed to investigate the impact of TBS on long-term outcomes after surgery.MethodsPatients who underwent radical-intent resection between June 2013 and December 2019 were retrospectively reviewed. Kaplan–Meier curves were used to analyze patient survival, and disease-free survival (DFS) and overall survival (OS) were examined in relation to TBS.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In recent years, there has been a growing interest in studies on TBS in PLC, making it a clinical research hotspot. The TBS model has demonstrated its prognostic risk stratification capabilities in hepatocellular carcinoma (HCC) [ 20 ], ICC [ 21 ], and combined hepatocellular − cholangiocarcinoma [ 22 ], while remaining user − friendly. Relevant studies have shown a strong correlation between radiological TBS and pathological TBS, with no significant difference observed in postoperative prediction ability [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in studies on TBS in PLC, making it a clinical research hotspot. The TBS model has demonstrated its prognostic risk stratification capabilities in hepatocellular carcinoma (HCC) [ 20 ], ICC [ 21 ], and combined hepatocellular − cholangiocarcinoma [ 22 ], while remaining user − friendly. Relevant studies have shown a strong correlation between radiological TBS and pathological TBS, with no significant difference observed in postoperative prediction ability [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%